Measurement Properties of the Brazilian-Portuguese Version of the Lumbar Spine Instability Questionnaire - Araujo, Amanda Costa; Menezes Costa, Luciola da Cunha; Soares de Oliveira, Crystian Bittencourt [UNESP]; Morelhao, Priscila Kalil [UNESP]; Negrao Filho, Ruben de Faria [UNESP]; Pinto, Rafael Zambelli [UNESP]; Pena Costa, Leonardo Oliveira (Lippincott Williams & Wilkins, 2017)
Study Design. Cross-cultural adaptation and analysis of measurement properties. Objective. To translate and cross-culturally adapt the Lumbar Spine Instability Questionnaire (LSIQ) into Brazilian-Portuguese and to test its measurement properties in Brazilian patients with low back pain. Summary of Background Data. The selection of subgroup of patients that respond better to specific interventions is the top research priority in the field of back pain. The LSIQ is a tool able to stratify patients with low back pain who responds better to motor control exercises. There is no Brazilian-Portuguese version of the LSIQ available. Methods. The original version of the LSIQ was translated and cross-culturally adapted. We collected data from 100 patients with low back pain. In addition to LSIQ, we also collected information about physical activity levels (measured by the International Physical Activity Questionnaire short version), disability (measured by the Roland Morris Disability Questionnaire), pain intensity (measured by the Pain Numerical Rating Scale), kinesiophobia (measured by the Tampa Scale of Kinesiophobia), and depression (measured by the Beck Depression Inventory). The measurement properties tested were internal consistency, reproducibility (reliability and agreement), construct validity, and ceiling and floor effects. Results. The Brazilian-Portuguese version of the LSIQ showed good measurement properties with a Cronbach alpha of 0.79, an intraclass correlation coefficient of 0.75, a standard error of measurement of 1.65 points, and a minimal detectable change of 3.54 points. We did not detect ceiling and floor effects. The construct validity analysis was observed a moderate correlation between the LSIQ and Pain Numerical Rating Scale r = 0.46, Roland Morris Disability Questionnaire r = 0.66, Tampa Scale of Kinesiophobia r = 0.49, and Beck Depression Inventory r = 0.44. Conclusion. The Brazilian-Portuguese version of LIQ has adequate measurement properties and can be used in clinical practice and research.
Keywords: instability; low back pain; measuring properties; questionnaire